Comparison of neoadjuvant single-agent treatment and dual-HER2 blockade for breast-conserving surgery conversion in HER2-positive breast cancer: a meta-analysis - Manlu Cui; Juan Fu; Qiuyun Li (BMC Cancer)
Abstract Background Neoadjuvant targeted therapy has shown that improve pathologic complete response and facilitate breast-conserving surgery, but the difference between single-agent treatment or dual-HER2 blockade to the conversion of breast-conserving surgery has not been well described. Methods Via the systematic literature search of PubMed, Web of Science and Cochrane Library databases, 5 eligible studies used to perform this meta-analysis, which was carried out using RevMan version 5.4. Results A total of 1306 patients from five randomized controlled trials were included in the analysis, revealing a significant increase in the conversion rate to breast-conserving surgery with neoadjuvant targeted therapy (OR 0.30, 95% CI 0.15–0.57; p = 0.0003). The odds ratio (OR) for single-agent treatment compared to dual-HER2 blockade was 1.04 (95% CI 0.73–1.48; p = 0.82). For pathological complete response (pCR), the OR for single-HER2 blockade versus dual-HER2 blockade was 0.43 (95% CI 0.34–0.55; p = 0.01), and for clinical response, it was 0.81 (95% CI 0.59–1.10; p = 0.17). The OR for serious adverse events between single-HER2 and dual-HER2 blockade was 0.72 (95% CI 0.55–0.95; p = 0.02). The risk ratio (RR) for pCR and the shift from mastectomy to BCS was 1.16 (95% CI 0.78–1.72; p = 0.47), while for clinical response and the shift from mastectomy to BCS, it was 2.40 (95% CI 1.44–4.01; p = 0.0008). Conclusion Neoadjuvant targeted treatment obviously promote the actual implementation rate of breast-conserving surgery, nevertheless, there was no statistically significant increase in single-agent treatment versus dual-HER2 blockade.